For a better world, ask "inconvenient" questions - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Democratic societies require the participation of its citizens in order to function. A quick, obligatory visit to the polling station counts, of course, but that may not be enough. If a country is "to achieve happiness, prosperity and progress", citizens must care enough to share their constructive views – and in the absence of that, ask "inconvenient questions". Speaking at SMU's Wee Kim Wee Centre Lunchtime Talks, Viswa Sadasivan, a Nominated Member of Parliament in Singapore, believes that such questions are necessary to "provoke and stimulate" the country's leaders to greater heights. --------------------------------------------------------------------------------